The Scattered Identity as a Comparative Analysis in the Turkish, Irish and Iraqi Novel: الهوية المبعثرة كتحليل مقارن في الرواية التركية والعراقية والايرلندية (مجلة ديالى للبحوث الانسانية, 2023)
The importance of this study is to zoom out the hidden facts and to show how circumstances effectively work in scattering the identity through a deep study of the cultures, especially in the literature of the contemporary novel. The theme of the scattered identity is highly analyzed by focusing on the share points in the selected novels. Writers like Elef Shafak from the Turkish Culture, Inaam Kachachi from the Iraqi culture and Anne Enright from the Irish culture. Based on the events in showing the suffering of the main characters in which the mentioned writers find fiction is the only way to escape from the grim reality of the modern life. The scattered identity theme is the common point in the selected works and the unified subject through sharing beliefs and drawing ideas to present concrete facts about how identity is really scattered and shattered in the contemporary literature.